Customer courtesy and service performance: The roles of self‐efficacy and social context. (8th April 2022) - Yoon, David J.; Muir (Zapata), Cindy P.; Yoon, Mahn Hee; Kim, Eugene
Summary: While the impact of negative customer treatment on service employees and their organizations is often emphasized in both scholarship and the popular press, relatively little work has examined the effects of customer courtesy . We draw on the social cognitive theory to theorize that customer courtesy can enhance service performance via its positive effect on employee self‐efficacy. Although getting customers to display courtesy may be outside an organization's direct control, we reason that management can amplify these benefits by establishing a strong organizational support climate. To examine our predictions, we developed a customer courtesy scale, then deployed it among service employees in the United States (Study 1) and hotel employees and their supervisors in East Asia (Study 2). We also collected experimental data (Study 3) to test our causal model. Across our studies, our data support the benefits of customer courtesy on employee self‐efficacy and, by extension, employee service performance. Moreover, our data reveal that when organizational support climate increases, the effect of customer courtesy on self‐efficacy and thus, service performance increases. Although it may be the case that bad is sometimes stronger than good, our work highlights the importance of positive workplace interactions (e.g., customer courtesy) on valued employee outcomes.